Crystal structures of native cytochrome c6 from Thermosynechococcus elongatus in two different space groups and implications for its oligomerization. Issue 9 (3rd September 2020) - Falke, Sven; Feiler, Christian; Chapman, Henry; Sarrou, Iosifina
Abstract : The structure of native cytochrome c 6 isolated from T. elongatus was solved by X‐ray crystallography and two different space groups were identified. The high‐resolution structures and complementary biophysical characterization in solution indicate interaction interfaces that could enable distinct functionality in photosynthesis. In addition, a post‐translational methylation is indicated. Abstract : Native cytochrome c 6 was purified from an extract of strain BP‐1 of the thermophilic cyanobacterium Thermosynechococcus elongatus . The protein was crystallized, and with only slight modifications of the buffer and vapour‐diffusion conditions two different space groups were observed, namely H 3 and C 2. Both crystal structures were solved; they contained three and six molecules per asymmetric unit and were refined to 1.7 and 2.25 Å resolution, respectively. To date, the structure of native cytochrome c 6 from T. elongatus has only been reported as a monomer using NMR spectroscopy, i.e. without addressing putative oligomerization, and related structures have only previously been solved using X‐ray crystallography after recombinant gene overexpression in Escherichia coli . The reported space groups of related cyanobacterial cytochrome c 6 structures differ from those reported here. Interestingly, the protein–protein interfaces that were observed utilizing X‐ray crystallography could also explain homo‐oligomerization in solution; specifically, trimerization is indicated by infra‐red dynamic light scattering and blue native gel electrophoresis in solution. Trimers were also detected by mass spectrometry. Furthermore, there is an indication of post‐translational methylation in the crystal structure. Additionally, the possibility of modifying the crystal size and the redox activity in the context of photosynthesis is shaping the investigated cytochrome as a highly suitable model protein for advanced serial crystallography at highly brilliant X‐ray free‐electron laser sources.